Livestock production in colonial Algeria and its contribution to foreign trade with France during the period (1870-1914) - abbas, houria (The Algerian Historical Journal, 2026)
This study summarizes some aspects of the colonial economic policy in Algeria during the period (1870-1914 AD) based on capitalist thought that France brought into the agricultural sector as a means for the development of societies. Hence the interest in animal breeding by the colon and worked to develop it and competed with the Algerians in their source of livelihood. The settlers’ interest in the animal barn in Algeria and the development of its census and the introduction of new breeds made them direct their animal production towards the French market in particular and foreign markets in general to ensure the permanence of serving the colonial economy based on the wealth of the settlement of Algeria and serving the metropolitan economy.